MOOCs at International Islamic University Malaysia - Ahmad Dahlan, Abdul Rahman; Juhari, Siti Sarah; Ahmad Shafiee, Anna Syafira (Research Publish Journals, 2015)
This paper looks at the perspective of developing an open learning website at International Islamic University Malaysia (IIUM). As a university that values excellence in teaching and learning practices, IIUM has to embark on initiatives that make use of the e-learning platforms. With this intention, IIUM’s MOOCs is to be a natural extension of its e-learning initiative, iTaleem. MOOCs at IIUM is designed to offer a taste of what learners may experience in a university’s program and they are not recreations of IIUM’s undergraduate courses. Islamic values are inculcated and embedded into all disciplines of knowledge.